David à Naples : une source pour le Saint Jérôme de Québec - Bédard, Sylvain (RACAR : Revue d'art canadienne / Canadian Art Review)

(untitled) (UAAC-AAUC (University Art Association of Canada | Association d'art des universités du Canada), 1990)
This article examines a work painted by David in Rome in 1779 when the artist was a pensioner of the King in the Academy of France (1775-80). An academic figure study on the theme of St. Jerome, the work was executed in the framework of assignments required of young pensioners at the time.Since its “reappearance” 40 years ago, the St. Jerome has received but little attention until now from Davidian criticism. An exception was Antoine Schnapper’s initial investigation of the work in an important article in the Revue du Louvre (1974) where he sought to establish a chronology of David’s works from his first stay in Rome. Schnapper noted for example the “strongly Caravaggesque character” of the painting, which he related to Ribera’s aesthetic and also to that of the Bolognese who often treated the subject, Guercino in particular. But this beginning, motivated especially by the picture’s clear affiliation with luminist painting of the seventeenth century, did not have a sequel, for no serious attempt has been made since to identify clearly a work that might have served David as a model.The author presents a stylistic comparison enabling him to place the St. Jerome in direct relation with a Ribera canvas painted in 1626 on the theme of St. Jerome and the angel of the Last Judgment. David was able to see this work during his trip to Naples in the summer of 1779, a sojourn that shortly preceded execution of the painting now in Québec. The present study is also concerned to locate the work within the artist’s production in Rome, thus underlining its importance to the formation of what is generally regarded as Davidian style.